2022
DOI: 10.3390/children9020189
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Supracondylar Humerus Fractures: Should We Avoid Surgery during After-Hours?

Abstract: Pediatric supracondylar humerus fractures occur frequently. Often, the decision has to be made whether to operate immediately, e.g., during after-hours, or to postpone until office hours. However, the effect of timing of surgery on radiological and clinical outcomes is unclear. This literature review with the PICO methodology found six relevant articles that compared the results of office-hours and after-hours surgery for pediatric supracondylar humerus fractures. The surgical outcomes of both groups in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Terpstra et al found that the incidence of paresthesia complicating ScHF treated between 9 p.m. and 2 a.m. was higher when compared to the incidence of nerve injuries observed in ScHF treated during office hours [11]. According to their literature review, it appears safe to postpone surgery to office hours, if circumstances are not optimal for acute surgery at nighttime and if there is no medical contraindication [11].…”
Section: Introductionmentioning
confidence: 99%
“…Terpstra et al found that the incidence of paresthesia complicating ScHF treated between 9 p.m. and 2 a.m. was higher when compared to the incidence of nerve injuries observed in ScHF treated during office hours [11]. According to their literature review, it appears safe to postpone surgery to office hours, if circumstances are not optimal for acute surgery at nighttime and if there is no medical contraindication [11].…”
Section: Introductionmentioning
confidence: 99%
“…The timing of treatment of fully displaced SCH fractures remains controversial. While many of these injuries can be safely postponed until the next day, 3,[24][25][26][27][28] all series have some fractures that still had overnight treatment, indicating that there are some of these fractures severe enough to warrant evening or overnight surgery. However, the guidance on which of these fully displaced modified Gartland type 3 or 4 injuries are best treated at night, and which can safely be postponed until the next day is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Baumann's angle [17][18][19][20] lateral rotation percentage, 18,21,22 location of the anterior humeral line as it crosses the capitellum (not touching, anterior edge, anterior third, middle third, posterior third; 18.22) were assessed. A "loss of reduction" was determined if any of the above metrics changed between the intraoperative and postoperative radiographs: (1) change of Baumann's angle > 12°1 3,23 (2) change of lateral rotation percentage of >25% 21 and (3) change of position of the anterior humeral line by at least two steps. 12…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contradicting reports exist. Farrow et al [ 20 ] and Schmid et al [ 21 ] suggested that postponing surgery is a safe method, and no difference in outcomes has been reported between daytime and night-time surgical treatment [ 22 ]. Accepted general practice involves fast-tracking operative treatment to avoid complications related to delayed management and subsequent soft tissue swelling.…”
Section: Discussionmentioning
confidence: 99%